Criminalization of Service Users and Traditional Commercial Sex Workers in Indonesia - Nining; A. Harits Nu’man; Oksidelfa Yanto; Neni Ruhaeni; Dini Dewi Heniarti (IJOLARES: Indonesian Journal of Law Research, 2024)
The urgency of law enforcement against service users and traditional commercial sex workers in Indonesia in handling the increasingly rampant practice of prostitution. Despite government efforts to discourage involvement in prostitution, the lack of specific regulations in Indonesian law has allowed service users of prostitution to avoid appropriate legal consequences. This research aims to criminalize both traditional commercial sex workers and service users using a legislative approach, conceptual approach, and comparative legal approach to address criminal issues faced by traditional commercial sex workers and users in Indonesia, one of which is the criminalization of all individuals involved in such practices, such as service users of prostitution who are not clearly regulated, although the government has made efforts through existing local regulations. The type of research used is juridical-normative or often referred to as doctrinal legal research. Several regions in Indonesia, such as DKI Jakarta, Indramayu Regency, Tangerang City, Denpasar City, Badung Regency in Bali, Batam City, and Bandung Regency, have issued local regulations criminalizing service users of prostitution in their respective areas. However, these regulations vary and impose lenient penalties on commercial sex workers and service users. Therefore, we need to study the Netherlands in addressing issues related to prostitution, which can ensnare both perpetrators and commercial sex workers.